"Z"‐Type Tilted Quasi‐One‐Dimensional Assembly of Actinide‐Embedded Coinage Metal Near‐Plane Superatoms and Their Optical Properties. Issue 9 (25th January 2023) - Huang, Wanrong; Yu, Famin; Zhu, Yu; Wang, Rui; Li, Jiarui; Zhang, Sean Xiao‐An; Wang, Zhigang
Abstract: In this work, a novel discovery that the coinage‐metal near‐plane superatoms (CM‐NPSs) formed by embedding actinide elements into the coinage metal rings can realize the "Z"‐type tilted quasi‐one‐dimensional (1D) direct assembly is reported. This success can be attributed to the strong bonding between the overlapping parts of adjacent superatomic motifs. First‐principles calculations reveal that the motifs maintain their geometric and electronic structures robustly during the assembly process. With the accumulation of motifs, the intensity of the absorption peak increases continuously in the ultraviolet‐visible (UV‐Vis) absorption spectra range of 300–450 nm, resulting in the hyperchromic effect, which is closely related to the degree of the participation of Th atoms. Furthermore, the absorption spectra show a continuously tunable feature in the 450–900 nm range, as the interlayer stacking pattern leads to a pronounced redshift. More importantly, the valence 5f‐shells of Th atoms have an increased contribution to the final orbitals of electronic transition, which demonstrates the advantages of the active high angular momentum electrons of actinide elements in spectral properties. These findings provide a valuable reference for the direct artificial assembly of near‐plane superatoms and optical properties of superatomic assemblies embedded with rare elements. Abstract : A novel "Z"‐type tilted quasi‐1D assembly strategy suitable for near‐plane superatoms, which attributes to the complex electronic structure of the central atom is devised. With the increase of the number of motifs, the physicochemical properties of the monomer are maintained without changing the assembly mode. In addition, the regularity and mechanism of UV‐Vis absorption spectra are also understood.